Respuesta :

[tex]\huge \bf༆ Answer ༄[/tex]

let's solve ~

[tex]{ \qquad{ \sf{ \dashrightarrow}}}  \:  \: \sf \:7x + 5y = - 56[/tex]

[tex]{ \qquad{ \sf{ \dashrightarrow}}}  \:  \: \sf \:5y = - 56 - 7x[/tex]

[tex]{ \qquad{ \sf{ \dashrightarrow}}}  \:  \: \sf \:y = \dfrac{1}{5} ( - 7x - 56)[/tex]

[tex]{ \qquad{ \sf{ \dashrightarrow}}}  \:  \: \sf \:y = - \dfrac{7}{5} x - \dfrac{56}{5} [/tex]

or

[tex]{ \qquad{ \sf{ \dashrightarrow}}}  \:  \: \sf \:y = - \bigg( \dfrac{7}{5} x + \dfrac{56}{5}\bigg) [/tex]

I hope it helped ~

ACCESS MORE